Perspectives of knowledge of bioethics by academics of health for professional activities - Biondo, Chrisne Santana (2018)
The objective of this research was to analyze the knowledge of bioethics by health academics in a public university in Bahia. This is a descriptive, exploratory study with a quantitative approach, carried out with 82 academics that were in the last semester of the health courses of the State University of the Southwest of Bahia - UESB. For the collection of data, the questionnaire on Formative Indicators in Bioethics in Health Professions was used: Survey. The data showed that the students present knowledge about the objectives and principles of bioethics, but when inferred about the concepts of bioethics, some participants presented divergences in the answers. It is concluded that the teaching of bioethics must be done in a transdisciplinary way, also requiring the dissociation of bioethics and deontology in the graduations, besides promoting spaces of reflection and knowledge about the subject.